(untitled) (Global Journal of Human-Social Science, 2022)
This article enhances the use of the applied game theory and hypergame theory in global politics and strategic security studies It suggests first a Deception Hypergame Model of Inter-state Conflict where conditions of certainty and uncertainty perception and deception are considered within a conflict war impediment perspective